2018
DOI: 10.1038/s41467-018-06134-z
|View full text |Cite
|
Sign up to set email alerts
|

STAT3-coordinated migration facilitates the dissemination of diffuse large B-cell lymphomas

Abstract: The motile characteristics and mechanisms that drive the dissemination of diffuse large B-cell lymphoma (DLBCL) are elusive. Here, we show that DLBCL initiates dissemination through activating STAT3-mediated amoeboid migration. Mechanistically, STAT3 activates RHOH transcription, which competes with the RhoGDP dissociation inhibitor RhoGDIγ to activate RhoA. In addition, activated STAT3 regulates microtubule dynamics and releases ARHGEF2 to activate RhoA. Both the JAK inhibitor ruxolitinib and the microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…The results of this study confirm literature data showing that STAT3 gene is a transcriptional target of BCL6 and that STAT3 is highly expressed and activated in ABC-DLBCL and BCL6-negative normal germinal center B cells [5]. Moreover, more recently, it has been demonstrated that DLBCL initiates dissemination through activating STAT3-mediated amoeboid migration [17].…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study confirm literature data showing that STAT3 gene is a transcriptional target of BCL6 and that STAT3 is highly expressed and activated in ABC-DLBCL and BCL6-negative normal germinal center B cells [5]. Moreover, more recently, it has been demonstrated that DLBCL initiates dissemination through activating STAT3-mediated amoeboid migration [17].…”
Section: Discussionsupporting
confidence: 89%
“…The aim of this study was the implementation of a simple T-GEP panel able to complement and improve COO-based prognostic stratification for routine clinical application. We designed a panel of genes corresponding to those of the Lymph2Cx assay for COO determination plus additional candidates selected because of their potential prognostic and/or therapeutic interest including MYC, BCL-2 and central nodes of NF-kB, Janus kinase (JAK)/signal transducer and activator of transcription (STAT), and phosphatidylinositol-3 kinase (PI3K) signaling 3,[28][29][30][31][32][33] . This panel of genes was applied to 186 DLBCLs enrolled in two recently reported large italian trials (DLCL04 and R-HDS0305) 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we assume that the Ca 2+ independent effect of Orai1/STIM1 on DLBCL cell migration could be mediated by protein–protein interactions, as previously described between TRPM8 channel and the small GTPase Rap1 causing endothelial cell migration inhibition [ 35 ]. More specifically, as previously demonstrated by Chen et al in solid cancer cells [ 18 ], we could hypothesize that after stimulation, the microtubule plus-end binding protein EB1 binds STIM1, linking it with microtubules and finally activating RhoA/ROCK-dependent cell migration [ 41 ]. Nevertheless, further experiments are needed to elucidate the exact molecular mechanism by which Orai1 and STIM1 interfere with DLBCL cell migration.…”
Section: Discussionmentioning
confidence: 87%